Low Caffeine (Decaffeine) Could Remembrance My Short-Term Memory: Effects of Caffeine on Short-Term Memory in Jabodetabek College Students - Tasya, Athiyya Rahmani Afiya; Pramesti, Adinda Anggun; Komarudin, Ardha Az Zahra; Putri, Wilda Zahara; Farisandy, Ellyana Dwi (Universitas Negeri Malang, 2023)
Caffeine is believed to improve a person's memory because a person can be awake and affect brain performance. The purpose of this study was to examine the effect of caffeine on short-term memory. This study uses a posttest control group design where two groups will be given treatment, and one group will not be given treatment. The participants of this study were 30 college students (Mage equals 19.4; SD equals 1.27) in Jabodetabek who consumed caffeine at least three times a week. Data collection using a digit span test adapted from Wechsler Adult Intelligence Scale (WAIS). The results showed that caffeine positively affected short-term memory in college students. Decaffeine has more effect on short-term memory than caffeine and mineral water. This research implies that college students can consume decaffeine to improve their short-term memory.